IL-10 and TNF-beta gene polymorphisms have no major influence on lactate levels after cardiac surgery - Říha, Hynek; Hubáček, Jaroslav; Poledne, Rudolf; Kellovský, Pavel; Březina, Aleš; Pirk, Jan (European journal of cardio-thoracic surgery, 2006)
OBJECTIVE: Lactate levels after cardiac surgery are influenced by different proinflammatory (TNF, IL-6, IL-8) and anti-inflammatory (IL-10) cytokines. The goal of the study was to determine the relationship between polymorphism in the IL-10 (-1082G/A) and TNF-beta (+252G/A) genes and lactate levels in patients after cardiac surgery. METHODS: We performed prospective observational study in 168 consecutive adult patients without left ventricle dysfunction undergoing elective coronary artery bypass grafting. Lactic acid levels were documented at five different time points: 10 min after beginning of cardiopulmonary bypass, 40 min after cardiopulmonary bypass termination, and 30 min, 8h, and 16 h after the surgery. Genetic analysis for polymorphism was performed by mismatched polymerase chain reaction and restriction analysis. RESULTS: No association was found between single polymorphism in IL-10 or TNF-beta gene and lactate levels, but the carriers of IL-10/TNF-beta genotype combination +A/GG had significantly different course of lactate levels in time with decrease in lactate (in comparison with increase in other groups) at 8h after the surgery. CONCLUSIONS: IL-10 (-1082G/A) and TNF-beta (+252G/A) gene polymorphisms have a little, yet measurable influence on the time course of changes in lactate levels after cardiac surgery.
Keywords: funkce levé komory srdeční; biologické markery; mediátory zánětu; lidé; Middle Aged; Adult; polymorfismus genetický; prospektivní studie; Inflammation Mediators; Female; Gene Frequency; Lactic Acid; Humans; Ventricular Function, Left; Polymorphism, Genetic; kyselina mléčná; Genotype; Interleukin-10; Prospective Studies; frekvence genu; lidé středního věku; Biomarkers; mužské pohlaví; koronární bypass; interleukin-10; genetická predispozice k nemoci; Coronary Artery Bypass; ženské pohlaví; Lymphotoxin-alpha; lymfotoxin-alfa; genotyp; Male; Aged; Postoperative Period; Genetic Predisposition to Disease; dospělí; senioři; pooperační období